Loan loss provisions and their effect on the profitability of commercial banks in nepal - Pramod Dahal; Dr. Rajesh Gurung; Sindhu Regmi; Ramjee Puri (Journal of Corporate Finance Management and Banking System, 2026)
An The study examines how the Loan Loss Provisions influence the profitability of commercial banks in Nepal in terms of the Return on Assets, and Return on Equity. Examining the data of 20 Nepalese commercial banks in 2000/01 to 2023/24, the study concludes that LLPs are significantly negatively correlated with ROA and ROE, which confirms that in spite of its pivotal role in ensuring financial stability, provisions directly lower the profitability in the short term. As the analysis also shows, Non-Performing Assets affect the profitability to a even greater extent than LLPs. However, the Credit to Deposit Ratio had no significant or even negative impact in the models. The research arrives at the conclusion that a balance of proper provisioning against risk and proactive NPA management is a necessary ingredient to both the stability of the Nepalese banks as well as its sustainable profitability.